Latroeggtoxin-VI protects nerve cells and prevents depression by inhibiting NF-κB signaling pathway activation and excessive inflammation - Wang, Haiyan; Zhai, Yiwen; Lei, Zhixiang; Chen, Si; Sun, Minglu; Yin, Panfeng; Duan, Zhigui; Wang, Xianchun (Frontiers in Immunology, 2023)
Depression has a high incidence and seriously endangers human health. Accumulated evidence indicates that targeting neuroinflammation is a potential avenue for neuroprotection and thus depression prevention. Herein, the effects of latroeggtoxin-VI (LETX-VI), a bioactive protein from the eggs of spider Latrodectus tredecimguttatus, on lipopolysaccharide (LPS)-induced inflammation and depression were systematically investigated using RAW264.7 macrophages and depression mouse model. Pretreatment with LETX-VI suppressed LPS-evoked NF-κB signaling pathway activation, inhibited LPS-induced over-production of NO, iNOS, IL-6 and TNF-α; at the same time LETX-VI mitigated the inhibitory effect of LPS on the expression of anti-inflammatory factors such as Arg-1, thereby suppressing oxidative stress and excessive inflammation. Culture of PC12 cells with the conditioned medium of RAW264.7 cells pretreated with LETX-VI demonstrated the neuroprotective effect of LETX-VI due to its anti-inflammation effect. In the LPS-induced depression mouse model, pretreatment with LETX-VI improved the LPS-induced depression-like behaviors, inhibited the activation of microglia and astrocytes, prevented the down-regulation of Nurr1 expression and alleviated the LPS-caused adverse changes in the brain tissues. Taken together, these in vitro and in vivo findings provide powerful insights into the anti-inflammation-based neuroprotective and antidepressant mechanisms of LETX-VI, which is helpful to deeply reveal the biological effects and potential applications of LETX-VI.